Analysis of cyclic frosting and defrosting of a vehicle heat pump - Jochen Westhaeuser; Henrik Schatz; Jan-Christoph Albrecht; Wilhelm Tegethoff; Nicholas Lemke; Juergen Koehler (International Journal of Refrigeration, 2023)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Regulation and role of the ER stress transcription factor CHOP in alveolar epithelial type-II cells - Oleksiy Klymenko; Martin Huehn; Jochen Wilhelm; Roxana Wasnick; Irina Shalashova; Clemens Ruppert; Ingrid Henneke; Stefanie Hezel; Katharina Guenther; Poornima Mahavadi; Christos Samakovlis; Werner Seeger; et al. (Journal of Molecular Medicine, 2019)

Lower body negative pressure enhances oxygen availability in the knee extensor muscles during intense resistive exercise in supine position - Dajana Parganlija; Vita Nieberg; Marc Sauer; Jörn Rittweger; Wilhelm Bloch; Jochen Zange (European Journal of Applied Physiology, 2019)

Stick or Dye: Evaluating a Solid Standard Calibration Approach for Point-Source Integrating Cavity Absorption Meters (PSICAM) - Jochen Wollschläger; Rüdiger Röttgers; Wilhelm Petersen; Oliver Zielinski (Frontiers in Marine Science, 2019)

Sedimentology and depositional sequences of a Kimmeridgian carbonate ramp system, Lower Saxony Basin, Northern Germany - Fanfan Zuo; Ulrich Heimhofer; Stefan Huck; Friedrich Wilhelm Luppold; Oliver Wings; Jochen Erbacher (Facies, 2018)

The Coastal Observing System for Northern and Arctic Seas (COSYNA) - Burkard Baschek; Friedhelm Schroeder; Holger Brix; Rolf Riethmüller; Thomas H. Badewien; Gisbert Breitbach; Bernd Brügge; Franciscus Colijn; Roland Doerffer; Christiane Eschenbach; Jana Friedrich; Philipp Fischer; et al. (Ocean Science, 2017)
The Coastal Observing System for Northern and Arctic Seas (COSYNA) was established in order to better understand the complex interdisciplinary processes of northern seas and the Arctic coasts in a changing environment. Particular focus is given to the German Bight in the North Sea as a prime example of a heavily used coastal area, and Svalbard as an example of an Arctic coast that is under strong pressure due to global change.The COSYNA automated observing and modelling system is designed to monitor real-time conditions and provide short-term forecasts, data, and data products to help assess the impact of anthropogenically induced change. Observations are carried out by combining satellite and radar remote sensing with various in situ platforms. Novel sensors, instruments, and algorithms are developed to further improve the understanding of the interdisciplinary interactions between physics, biogeochemistry, and the ecology of coastal seas. New modelling and data assimilation techniques are used to integrate observations and models in a quasi-operational system providing descriptions and forecasts of key hydrographic variables. Data and data products are publicly available free of charge and in real time. They are used by multiple interest groups in science, agencies, politics, industry, and the public.

Validating the prediction accuracies of marker-assisted and genomic selection of Fusarium head blight resistance in wheat using an independent sample - Yong Jiang; Albert Wilhelm Schulthess; Bernd Rodemann; Jie Ling; Jörg Plieske; Sonja Kollers; Erhard Ebmeyer; Viktor Korzun; Odile Argillier; Gunther Stiewe; Martin W. Ganal; Marion S. Röder; et al. (Theoretical and Applied Genetics, 2017)

High-resolution monitoring of marine protists based on an observation strategy integrating automated on-board filtration and molecular analyses - Katja Metfies; Friedhelm Schroeder; Johanna Hessel; Jochen Wollschläger; Sebastian Micheller; Christian Wolf; Estelle Kilias; Pim Sprong; Stefan Neuhaus; Stephan Frickenhaus; Wilhelm Petersen (Ocean Science, 2016)
Information on recent biomass distribution and biogeography of photosynthetic marine protists with adequate temporal and spatial resolution is urgently needed to better understand the consequences of environmental change for marine ecosystems. Here we introduce and review a molecular-based observation strategy for high-resolution assessment of these protists in space and time. It is the result of extensive technology developments, adaptations and evaluations which are documented in a number of different publications, and the results of the recently completed field testing which are introduced in this paper. The observation strategy is organized at four different levels. At level 1, samples are collected at high spatiotemporal resolution using the remotely controlled automated filtration system AUTOFIM. Resulting samples can either be preserved for later laboratory analyses, or directly subjected to molecular surveillance of key species aboard the ship via an automated biosensor system or quantitative polymerase chain reaction (level 2). Preserved samples are analyzed at the next observational levels in the laboratory (levels 3 and 4). At level 3 this involves molecular fingerprinting methods for a quick and reliable overview of differences in protist community composition. Finally, selected samples can be used to generate a detailed analysis of taxonomic protist composition via the latest next generation sequencing technology (NGS) at level 4. An overall integrated dataset of the results based on the different analyses provides comprehensive information on the diversity and biogeography of protists, including all related size classes. At the same time the cost of the observation is optimized with respect to analysis effort and time.

Genomic selection in a commercial winter wheat population - Sang He; Albert Wilhelm Schulthess; Vilson Mirdita; Yusheng Zhao; Viktor Korzun; Reiner Bothe; Erhard Ebmeyer; Jochen C. Reif; Yong Jiang (Theoretical and Applied Genetics, 2016)

Multiple-trait- and selection indices-genomic predictions for grain yield and protein content in rye for feeding purposes - Albert Wilhelm Schulthess; Yu Wang; Thomas Miedaner; Peer Wilde; Jochen C. Reif; Yusheng Zhao (Theoretical and Applied Genetics, 2016)

Flow-through PSICAM: a new approach for determining water constituents absorption continuously - Jochen Wollschläger; Maik Grunwald; Rüdiger Röttgers; Wilhelm Petersen (Ocean Dynamics, 2013)

Claudin-11 is over-expressed and dislocated from the blood–testis barrier in Sertoli cells associated with testicular intraepithelial neoplasia in men - Cornelia Fink; Roswitha Weigel; Ludger Fink; Jochen Wilhelm; Sabine Kliesch; Martina Zeiler; Martin Bergmann; Ralph Brehm (Histochemistry and Cell Biology, 2009)

Altered tension cost in (TG(mREN-2)27) rats overexpressing the mouse renin gene - Carsten Zobel; Persephone Zavidou-Saroti; Birgit Bölck; Klara Brixius; Hannes Reuter; Konrad Frank; Holger Diedrichs; Jochen Müller-Ehmsen; Wilhelm Bloch; Robert H. G. Schwinger (European Journal of Applied Physiology, 2006)

Volatiles modulate the development of plant pathogenic rust fungi - Kurt Mendgen; Stefan G. R. Wirsel; Andreas Jux; Jochen Hoffmann; Wilhelm Boland (Planta, 2006)